Portal Hypertension: Integrated Internal Medicine Management with Laboratory Evaluation, Radiologic Assessment, and Family Medicine–Based Longitudinal Care - Aldosari, Moneef Mansour; Ghada Zaal Alrowaili; Othman Mohammed Almousa; Abada Awaji Hakami; Essa Hassan Essa Abu Alzwaid; Amin Ibrahim Ahmed Otaif; Amal Ali Soliman Gahtani; Hussen Bahws Saeed Alhsnani; Mohd Husain Mobarki; Salem Ali Aldhafeeri; Salman Mkazi Sulaiman Alshammri (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Portal hypertension is a major hemodynamic consequence of chronic liver disease and other hepatic or extrahepatic disorders. It drives complications such as variceal bleeding, ascites, and encephalopathy, significantly impacting morbidity and mortality. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> To provide an integrated review of portal hypertension, emphasizing pathophysiology, diagnostic strategies, and multidisciplinary management. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A comprehensive synthesis of current evidence and guidelines was performed, covering hemodynamic principles, etiologic classification, laboratory and imaging evaluation, and therapeutic approaches including pharmacologic, endoscopic, and interventional strategies. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Portal hypertension arises from increased intrahepatic resistance and augmented splanchnic inflow, leading to collateral formation and systemic circulatory changes. Clinically significant portal hypertension (HVPG ≥10 mm Hg) predicts decompensation, while ≥12 mm Hg correlates with variceal bleeding risk. Noninvasive tools such as elastography and Doppler ultrasound complement invasive HVPG measurement. Management integrates etiologic therapy, nonselective beta-blockers (preferably carvedilol), endoscopic prophylaxis, and escalation to TIPS or transplantation for refractory complications. Preventive strategies—alcohol abstinence, metabolic optimization, and early antiviral therapy—remain pivotal. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Portal hypertension is a multifactorial syndrome requiring early detection, risk stratification, and coordinated care across specialties. Evidence-based interventions targeting both underlying disease and portal pressure reduction improve survival and quality of life.